Alpha-L-fucosidase as a putative prognostic biomarker in breast cancer - Z. M. A. A. Hamodat; H. H. Abdulwahhab; A. R. M. T. Hamodat (The Ukrainian Biochemical Journal, 2024)
Search for reliable biomarkers for predicting progression of breast cancer is essential in managing the disease. So, we are trying to provide new insights into the potential role of alpha-fucosidase (AFU) as a putative prognostic biomarker in breast cancer as compared to classic markers. The study included 56 women with breast cancer; 25 had early breast cancer, and the rest (31) had metastatic breast cancer. Thirty healthy women were considered a control group. Early breast cancer patients had a significantly increased (P ≤ 0.0001) AFU level compared with the control group. A non-significant difference in the De-ritis ratio appeared for early breast cancer compared with control. Metastatic breast cancer had a significantly (P ≤ 0.0001) increased AFU and De-ritis ratio compared with early breast cancer and the control group. A positive significant (P = 0.01) correlation exists between AFU level, age factor (r = 0.295), and the De-ritis ratio in breast cancer patients. We can conclude that it is possible to consider alpha-L-fucosidase (AFU) as a putative prognostic biomarker in breast cancer more potent than the ratio of De-Ritis. Moreover, the coincidence of elevated AFU and De-ritis levels in metastatic breast cancer gives us an idea of the stage of the disease.